1992
DOI: 10.1677/joe.0.1350311
|View full text |Cite
|
Sign up to set email alerts
|

Milking frequency alters the milk yield and mammary blood flow response to intra-mammary infusion of insulin-like growth factor-I in the goat

Abstract: The milk yield and mammary blood flow responses to close-arterial, intra-mammary infusion of IGF-I were investigated in five Saanen goats milked frequently or normally the day before. Animals were infused for 6 h with recombinant human IGF-I (1.3 nmol/min) and milked hourly following i.v. injection of oxytocin beginning 2 h before infusion and then every 2 h. On one occasion animals were milked five times (after i.v. injection of oxytocin) on the day before infusion and on the other they were milked twice, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…It is plausible that the decrease in expression of IGFBPs could increase the bioavailability of IGF-I in the 4×-milked mammary tissues, which could be one factor contributing to the higher level of proliferation previously reported in 4×-milked mammary tissues (Murney et al, 2015a). The idea of downregulation of IGFBPs in the mammary gland in response to increased MF, increasing the bioavailability of IGF-I, may also explain the results obtained by Prosser and Davis (1992). The study conducted by Prosser and Davis (1992) demonstrated that lactogenic effects of close arterial infusion of IGF-I into the mammary gland in goats is not apparent if an increased MF treatment is applied to the mammary gland on the day preceding infusion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is plausible that the decrease in expression of IGFBPs could increase the bioavailability of IGF-I in the 4×-milked mammary tissues, which could be one factor contributing to the higher level of proliferation previously reported in 4×-milked mammary tissues (Murney et al, 2015a). The idea of downregulation of IGFBPs in the mammary gland in response to increased MF, increasing the bioavailability of IGF-I, may also explain the results obtained by Prosser and Davis (1992). The study conducted by Prosser and Davis (1992) demonstrated that lactogenic effects of close arterial infusion of IGF-I into the mammary gland in goats is not apparent if an increased MF treatment is applied to the mammary gland on the day preceding infusion.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, IGF-I has been shown to increase milk secretion in goats when administered via close arterial injection (Prosser et al, 1990). Interestingly, this effect is masked by a preceding treatment of increased MF, suggesting some link between the effect of IGF-I and the effect of MF (Prosser and Davis, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it seems that the actions of IGF-I and GH on milk production differ depending on frequency of milking. If goats are milked at frequent intervals, the galactopoietic response to IGF-I is abolished (Prosser and Davis, 1992), whereas the response to bST is not (Davis et al, 1991). Finally, neither IGF-I nor IGF-II was able to reinstate lactation in rats treated with anti-somatotropin antibodies (Flint et al, 1992(Flint et al, , 1994.…”
Section: Insulin-like Growthmentioning
confidence: 99%
“…However, this did not alter the rate of milk secretion. Based on these experiments, together with earlier studies with growth hornone treatment (Mepham, Lawrence, Peters & Hart, 1984) and close-arterial infusion of insulin-like growth factor-I (Prosser & Davis, 1992), which also increased mammary blood flow without a concomitant alteration in milk yield, it would seem that mlammary hyperaemia is not sufficient by itself to increase milk yield in the normally lactating goat during mid-, or postpeak, lactation.…”
Section: Discussionmentioning
confidence: 87%